2019
DOI: 10.1212/nxi.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying therapies alter gut microbial composition in MS

Abstract: ObjectiveTo determine the effects of the disease-modifying therapies, glatiramer acetate (GA) and dimethyl fumarate (DMF), on the gut microbiota in patients with MS.MethodsParticipants with relapsing MS who were either treatment-naive or treated with GA or DMF were recruited. Peripheral blood mononuclear cells were immunophenotyped. Bacterial DNA was extracted from stool, and amplicons targeting the V4 region of the bacterial/archaeal 16S rRNA gene were sequenced (Illumina MiSeq). Raw reads were clustered into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 39 publications
1
70
3
1
Order By: Relevance
“…In EAE, GA administration ameliorated the disease phenotype coupled with an increase in gut Prevotella, and the administration of GA combined with GI colonization with live Prevotella led to the further attenuation of disease [83]. GA treatment in patients with MS was shown to exert an effect in the relative abundance of gut microbiota, especially the Lachnospiraceae and Veillonellaceae families [76]. Similarly, another case-control study in patients with RRMS treated with GA reported alterations in the relative composition of the gut microbiome with respect to several Clostridium [84].…”
Section: Glatiramer Acetatementioning
confidence: 99%
See 2 more Smart Citations
“…In EAE, GA administration ameliorated the disease phenotype coupled with an increase in gut Prevotella, and the administration of GA combined with GI colonization with live Prevotella led to the further attenuation of disease [83]. GA treatment in patients with MS was shown to exert an effect in the relative abundance of gut microbiota, especially the Lachnospiraceae and Veillonellaceae families [76]. Similarly, another case-control study in patients with RRMS treated with GA reported alterations in the relative composition of the gut microbiome with respect to several Clostridium [84].…”
Section: Glatiramer Acetatementioning
confidence: 99%
“…Clinical data stemming from metagenomics analysis of gut microbiota alterations in patients receiving DMF and glatiramer acetate (GA) further verified that DMTs exert a profound effect on the relative composition of gut microbiota. The above could shed light into potential additional mechanisms of action [76].…”
Section: Disease-modifying Treatment (Dmt) and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Alle diese Studien zeigen konsistent eine veränderte Zusammensetzung des Mikrobioms von MS-Patienten gegenüber Kontrollen, bleiben aber rein deskriptiv. Auch die immunmodulatorische Therapie der MS ist in der Lage, das Mikrobiom zu verändern [16]. Auffällig ist vor allem die große Varianz der Ergebnisse, sodass fast jede Studie zu einem anderen Ergebnis hinsichtlich der mit MS-assoziierten Mikrobiomveränderungen kam.…”
Section: Rolle Des Mikrobioms Und Darms Bei Msunclassified
“…[43][44][45][46] However, previous human studies were limited by small sample sizes, enrollment of patients with longer disease duration, and confounding effects of immunomodulatory therapy, thus precluding conclusions regarding the causal influence of the gut microbiome on the MS immune system, or in other words, leaving the "chicken or egg dilemma" unresolved. 47 Katz Sand et al 48 investigated in a crosssectional study the effects of 2 widely used disease-modifying drugs, glatiramer acetate (GA) and dimethyl fumarate (DMF), on gut microbial composition. Stool samples from 168 participants with MS from 2 MS centers (75 treatment naive, 33 on DMF, and 60 on GA) were collected, and 16S rRNA amplicon sequencing was performed in parallel with immunophenotyping from patients' whole blood (at 1 center only) to validate the expected effects of DMF and GA.…”
mentioning
confidence: 99%